Global body posture evaluation in patients with temporomandibular joint disorder (Clinics, 2009)
AIM: To identify the relationship between anterior disc displacement and global posture (plantar arches, lower limbs, shoulder and pelvic girdle, vertebral spine, head and mandibles). Common signs and symptoms of anterior disc displacement were also identified. INTRODUCTION: Global posture deviations cause body adaptation and realignment, which may interfere with the organization and function of the temporomandibular joint. METHODS: Global posture evaluation was performed in a group of 10 female patients (20 to 30 years of age) with temporomandibular joint disc displacement and in a control group of 16 healthy female volunteers matched for age, weight and height. Anterior disc displacement signs, symptoms and the presence of parafunctional habits were also identified through interview. RESULTS: Patients with disc displacement showed a higher incidence of pain in the temporomandibular joint area, but there were no differences in parafunctional habits between the groups. In the disc displacement group, postural deviations were found in the pelvis (posterior rotation), lumbar spine (hyperlordosis), thoracic spine (rectification), head (deviation to the right) and mandibles (deviation to the left with open mouth). There were no differences in the longitudinal plantar arches between the groups. CONCLUSION: Our results suggest a close relationship between body posture and temporomandibular disorder, though it is not possible to determine whether postural deviations are the cause or the result of the disorder. Hence, postural evaluation could be an important component in the overall approach to providing accurate prevention and treatment in the management of patients with temporomandibular disorder.